Seed vigor testing by low temperature germination in early rice - CAO Dongdong; WU Wei; CHEN Shanyu; QIN Yebo; RUAN Guanhai; LU Min; QIAN Peili; HUANG Yutao (浙江大学学报. 农业与生命科学版)
Taking the seeds of six early rice cultivars ‘Zhuliangyou 06’, ‘Zhuliangyou 101’, ‘Zhongzao 39’, ‘Jinzao 47’, ‘Zhongjiazao 17’ and ‘Yongxian 15’ as materials, the seed vigor of these early cultivars was determinated by the standard germination test, low temperature germination test (12 ℃, 15℃ and 18 ℃) and field emergence test. The results showed that the germination percentages at 18℃ after 4-5 days and 15℃ after 5-7 days had significantly positive relationship to the field emergence (FE). Especially, the correlation coefficient between germination percentage at 18℃ after 4 days and FE reached 0.932, revealing a fast and accurate method for measuring the seed vigor at a low temperature. The endogenous ABA content of seed at 18℃ after 4 days were negatively related to the germination percentages and FE. The real-time fluorescence quantitative polymerase chain reaction analysis showed the expression levels of ABA-synthesis related genes in high-vigor seeds were significantly lower than those in the low-vigor seeds. However, the most genes involved in ABA-catabolism and signal transduction related genes were highly expressed in the high-vigor seeds. Different responses in ABA metabolism and chilling signal transduction to low temperature stress might explain the seed vigor differences in the 12 early rice seed samples. The present study further reveals the internal mechanism of low temperature stress regulating seed vigor of early rice, which could provide a new theoretical basis for testing seed vigor of early rice with low temperature germination test.